Development of Augmented Reality-Based Science Learning Media to Improve Creative Thinking Skills and Digital Literacy in Junior High School Students - Pakereng, Yolanda H. I.; Billi, Susanti; Walla, Yulius Ndara; Ghunu, Angela (Education and Development Research, 2026)
21st-century skills that students need to have are creative thinking skills and digital literacy. Efforts to improve creative thinking skills and digital literacy can be done through the development of Augmented Reality (AR)-based learning media. Augmented Reality is a current technology that combines real objects (the physical world) with the digital world and will obtain clear and detailed information from objects that are made as if alive. In the field of education, the use of Augmented Reality can produce interesting learning media and facilitate the student learning process. Based on the results of observations conducted on students, the empowerment of creative thinking skills and digital literacy has not been optimally implemented. However, basically the school has recognized the importance of empowering creative thinking skills and digital literacy for students. Creative thinking skills and digital literacy that have not been optimally implemented are not supported by the availability of learning media, especially in science subjects that are in accordance with facts or real objects around them. Creative thinking skills and digital literacy are not optimal and there is no development of science learning media that activates students so that researchers conducted research to develop AR learning media. The purpose of this research is to develop AR-based science learning media to improve creative thinking skills and digital literacy of eighth-grade students. The research and development method is the Lee and Owens method. Results indicate AR learning media developed can improve creative thinking skills and digital literacy of grade 8 students.